2009
DOI: 10.1186/1477-7827-7-127
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ERbeta immunoexpression and apoptosis in the germ cells of cimetidine-treated rats

Abstract: BackgroundCimetidine, refereed as antiandrogenic drug, causes hormonal changes in male patients such as increased testosterone and FSH levels. In the rat testis, structural alterations in the seminiferous tubules have been related to germ cell loss and Sertoli cell death by apoptosis. Regarding the important role of Sertoli cells in the conversion of testosterone into estrogen, via aromatase, the immunoexpression of estrogen receptors-beta (ERbeta) was evaluated in the germ cells of untreated and treated rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
4
19
1
Order By: Relevance
“…Our current finding of the ERb absence in germ cells differs from the reports of other authors who found ERb-immunopositivity in gonocytes, spermatogonia, pachytene spermatocytes, round and elongated spermatids [47,48]. These discrepancies could be explained by the data of Carreau and Hess [1] who described testicular ERb-expression to be dependent on species, subjects within one species as well as preservation techniques and antibodies used for immunohistochemistry.…”
Section: Discussioncontrasting
confidence: 57%
“…Our current finding of the ERb absence in germ cells differs from the reports of other authors who found ERb-immunopositivity in gonocytes, spermatogonia, pachytene spermatocytes, round and elongated spermatids [47,48]. These discrepancies could be explained by the data of Carreau and Hess [1] who described testicular ERb-expression to be dependent on species, subjects within one species as well as preservation techniques and antibodies used for immunohistochemistry.…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, ER ␤ immunolabelling was observed in different germ cell types, including PGCs, and also in Leydig cells in animals collected during summer. The presence of ER ␤ in the male reproductive system has been documented in Leydig cells [Carreau and Hess, 2010] as well as in different cells of germinal lineage, including the spermatogonia of different mammal species [van Pelt et al, 1999;Sasso-Cerri, 2009;Carreau and Hess, 2010] and amphibians [Arenas et al, 2001]. The presence of ERs in a determined cell indicates a direct action of estrogen in this cell [Berensztein et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated the important role of estrogen on the spermatogenic process including germ cell proliferation, differentiation, the final maturation of spermatids as well as germ cell survival and apoptosis [Sasso-Cerri, 2009;Carreau and Hess, 2010]. The irreversible conversion of androgens into estrogens is catalyzed by the cytochrome P450 aromatase enzyme, a product of a unique gene called Cyp19 [Simpson et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A later in vivo system study conducted by Sasso-Cerri and Miraglia [48] found that cimetidine may lead to detachment and apoptosis of Sertoli cells and thus affect negatively sperm quality. In 2009, Sasso-Cerri confirmed these findings and showed that cimetidine at the same concentration enhances oestrogen receptor beta, a nuclear receptor activated by the sex hormone oestrogen, immunoexpression and apoptosis in germ cells of adult male rats [49]. H2RA, histamine-2 receptor antagonist.…”
Section: Effect Of Cimetidinementioning
confidence: 86%